The potential of novel gentamicin-black seed oil (GBSO) fusion emulsion in treating biofilm infection - Mohd Shafri, Mohd Affendi; Yaacob, Khairul Ikhwan; Yusof, Fathin Athirah; Shahdan, Intan Azura; Mohd Yusof, Nazri; Mohamed, Farahidah (2015)
Widely-used osteomyelitis antibiotic, Gentamicin, was fused with the oil of Black Seed, to form an emulsion and tested for its antimicrobial and antibiofilm properties on an osteomyelitis clinical isolate of S.aureus and a control S.aureus ATCC 29213. The Broth Microdilution Method was used to determine the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). Briefly, serial dilution of GBSO emulsions was performed on 96 well microtitre plate with each well containing 100 μL bacterial suspension at 108 cfu/ml and incubated for 24 hours at 37°C. The OD reading of each well was taken as the MIC. Content of the well that showed no sign of growth was inoculated on Tryptic Soy Agar (TSA) and incubated overnight for MBC value determination. Next, the effect of the GBSO emulsion on biofilm thickness and viability of bacteria within biofilm was assessed using confocal laser scanning microscope (CLSM). Biofilm of S.aureus, formed on coverslips within 24 hours, were first exposed to GBSO emulsions for 24 hours. After that, all treated biofilm were stained with Live/Dead Baclight stain, viewed with CLSM and images were analyzed using Image J software. In summary, the GBSO emulsion have significantly low MIC and MBC value compared to Gentamicin, and significantly low MBC compared to the Black Seed oil. CLSM analysis showed significant reduction in the thickness of biofilm and highest surface percentage of non-viable (dead) bacteria compared to Gentamicin and N.sativa alone on both strains of S.aureus (clinical isolate and control) after treatment with the GBSO emulsion.